Abnormal Speech Spectrum and Increased Pitch Variability in Young Autistic Children - Bonneh, Yoram S.; Levanon, Yoram; Dean-Pardo, Omrit; Lossos, Lan; Adini, Yael (Frontiers in Human Neuroscience, 2011)
Children with autism spectrum disorder (ASD) who can speak often exhibit abnormal voice quality and speech prosody, but the exact nature and underlying mechanisms of these abnormalities, as well as their diagnostic power are currently unknown. Here we quantified speech abnormalities in terms of the properties of the long-term average spectrum (LTAS) and pitch variability in speech samples of 83 children (41 with ASD, 42 controls) ages 4-6.5 years, recorded while they named a sequence of daily-life pictures for 60 sec. We found a significant difference in the group’s average spectra, with ASD spectra being shallower and exhibiting less harmonic structure. Contrary to the common impression of monotonic speech in autism, the ASD children had a significantly larger pitch range and variability across time. A measure of this variability, optimally tuned for the sample, yielded 86% success (90% specificity, 80% sensitivity) in classifying ASD in the sample. These results indicate that speech abnormalities in ASD are reflected in its spectral content and pitch variability. This variability could imply abnormal processing of auditory feedback or elevated noise and instability in the mechanisms that control pitch. The current results are a first step towards developing speech-spectrum-based bio-markers for early diagnosis of ASD.